2023
DOI: 10.1210/clinem/dgad072
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Receptor-β Agonists in NAFLD Therapy: Possibilities and Challenges

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a progressive metabolic liver disease with an unknown pathogenesis and no FDA-approved drug treatment to date. Hypothyroidism has been identified as a risk factor for NAFLD as thyroxine is required for regulating metabolism in adults. Thyroxine has been shown to reduce fat in the livers of murine models with experimentally induced NAFLD. The use of synthetic thyroxine has been shown to increase lipid metabolism leading to weight loss; however, thyroxine has also been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…Understanding the specific underlying mechanistic pathways is crucial. 11 It is true that NAFLD and hypothyroidism share common clinical features, including obesity, insulin resistance and dyslipidaemia. To the best of our knowledge, we are the first group to evaluate physiologically relevant hormonal systems, such as leptin and adiponectin, which can better reflect total fat mass and central obesity, respectively, than typical anthropometric measurements, 17 as well as total GDF-15, a stress hormone/mitokine recently suggested to be involved in NAFLD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the specific underlying mechanistic pathways is crucial. 11 It is true that NAFLD and hypothyroidism share common clinical features, including obesity, insulin resistance and dyslipidaemia. To the best of our knowledge, we are the first group to evaluate physiologically relevant hormonal systems, such as leptin and adiponectin, which can better reflect total fat mass and central obesity, respectively, than typical anthropometric measurements, 17 as well as total GDF-15, a stress hormone/mitokine recently suggested to be involved in NAFLD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism is probably the best characterized endocrine disorder associated with NAFLD and steatohepatitis, possibly due to underlying associations with lipid metabolism 4,6–9 ; lipotoxicity in hepatocytes is a key driver and one of the most important characterizing features in NAFLD 10 . The role of thyroid axis in liver health is universally acknowledged in the literature—albeit with occasional conflicting data 3,11 . The latter are potentially attributable to small study size limiting power, variations in NAFLD diagnostic methodologies—arising from the absence of the utilization of the diagnostic gold standard for NAFLD—and lack of histological evaluation of more advanced stages such as at‐risk NASH 7,12 .…”
Section: Introductionmentioning
confidence: 99%
“… 34 In human studies, low-dose TH as well as two liver-specific THRβ specific agonists VK-2809/MB-07811 and resmetirom (MGL-3196) have shown significant efficacy in resolving MASLD/MASH. 35 , 36 The pivotal phase 3 MAESTRO-NASH clinical trial with Madrigal Pharmaceuticals’ oral MASH therapy, resmetirom, robustly demonstrated a significant reduction in hepatic fat and inflammation in patients with MASH. This treatment has received the United States Food and Drug Administration (FDA) breakthrough therapy designation.…”
Section: Nuclear Hormone Receptors and Mashmentioning
confidence: 99%
“…As a result, thyroid-hormone-based treatments, including resmetirom [14], are an attractive therapeutic target in patients with NAFLD and NASH. Two THR subtypes are found in the human body: THR-α, which is predominantly expressed in cardiac tissue, and THR-β, which is most commonly found in the liver and is responsible for the intrahepatic response to T3 [115]. THR-β is a critical receptor in the regulation of cholesterol metabolism and fatty acid oxidation, as exhibited in mouse models [79,116].…”
Section: Thyroid Receptor (Thr)-βmentioning
confidence: 99%